A review of technologies and techniques for indoor positioning systems - Awang Md Isa, Azmi; Manap, Zahariah; Darsono, Abd Majid; Zainuddin, Suraya (Human Resource Management Academic Research Society, 2025)
Location-based services are among important applications in current telecommunication networks which causes an increasing demand in the advancements of indoor positioning systems (IPS). This paper presents a comprehensive review of the technologies and techniques employed in recent works related to IPS and discusses the challenges in IPS implementations. This study widely categorizes indoor positioning technologies into five types which are computer vision, short-range communication, acoustic-based, magnetic methods, and radio frequency (RF) technologies. The strengths and limitations of each technology is discussed based on its accuracy, coverage, infrastructure, implementation cost and signal characteristics. The literature study shows that range-based and fingerprinting are two main techniques employed in IPS. In addition, the study indicates that fingerprinting methods utilizing Wi-Fi and cellular networks are prevalent due to their widespread availability. However, these technologies face some challenges such as multipath fading, signal instability, device heterogeneity, infrastructure and cost implications, computational complexity, and privacy and security concerns. This paper emphasizesthe need for innovative approaches to enhance positioning accuracy and reduce infrastructure costs, thereby fostering broader adoption of IPS across diverse applications.